Pola Aktivitas Dan Pemanfaatan Ruang Desa Wisata Lerep Pada Era New Normal - Eppy Yuliani (Universitas Islam Sultan Agung Semarang, 2022)
AbstractThe tourism sector in Indonesia has doubled in the last decade, and in 2017 it was recorded that tourist visits reached 15 million people. The tourism industry has the potential to develop and become an economic driver so that it becomes a priority in development. Several tourist objects, both large-scale and village-scale, have had an impact on increasing the economic growth of the community. However, with the occurrence of the Covid 19 pandemic, since March 2020, government policies, both central and regional, have emerged in an effort to overcome the Covid 19 pandemic which prohibits and limits the operation of tourist destinations, including tourist villages. As a result, many tourism activities are not operating. This of course has an impact on the income of tourism business actors. However, when the Covid 19 pandemic had subsided, several tourist activities had started operating. This period is known as the New Normal Era, where a condition applies health protocols to all community activities, including tourism activities. Research questions, are there any changes in community activities in the Tourism Village, and how is the space utilized. This study aims to determine the pattern of community activities and the use of space in the Lerep Tourism Village in the New Normal era. The research location is in Lerep Tourism Village, West Ungaran District, Semarang Regency. The research methodology uses a rationalistic qualitative approach, through in-depth interviews and qualitative descriptive analysis techniques. This research is important to do, it is hoped that this research can describe the activity patterns of the tourism village community actors, and can describe/map the use of space in Lerep Village during the pandemic.AbstrakSektor pariwisata di Indonesia telah tumbuh dua kali lipat dalam satu dekade terakhir, dan tahun 2017 tercatat kunjungan wisata mencapai 15 juta orang. Industri pariwisata menjadi sangat potensial berkembang dan menjadi penggerak ekonomi sehingga menjadi prioritas dalam pembangunan. Beberapa obyek wisata baik skala besar maupun skala desa memberikan dampak peningkatan tumbuhnya perekonomian masyarakat. Namun dengan terjadinya pandemi Covid 19, sejak bulan Maret 2020 muncul kebijakan-kebijakan pemeritah baik pusat maupun daerah dalam upaya mengatasi pandemi Covid 19 yang melarang dan membatasi operasional destinasi wisata, termasuk Desa wisata. Dampknya banyak aktivitas pariwisata tidak beroperasi . Hal ini tentu saja berimbas terhadap pendapatan para pelaku usaha pariwisata. Namun ketika pandemi Covid 19 sudah mereda, beberapa aktivitas wisata sduah mulai beroperasi. Periode ini dikenal dengan Era New Normal, dimana suatu kondisi yang menerapkan protokol kesehatan pada semua aktivitas masyarakat, termasuk aktivitas wisata. Pertanyaan penelitian, apakah ada perubahan aktivitas masyarakat di Desa Wisata, dan bagaimana pemanfaatn ruang nya. Penelitian ini bertujuan mengetahui pola aktivitas masyarakat dan pemnafaatan ruang di Desa Wisata Lerep pada era New Normal. Lokasi penelitian di Desa Wisata Lerep, Kecamatan Ungaran barat, Kabupaten Semarang. Metodologi penelitian dengan pendekatan kualitatif rasionalistik, melalui indepth interview dan teknik analisis deskriptif kualitatif. Penelitian ini penting dilakukan, diharapkan dari penelitian ini dapat menggabarkan pola aktivitas masyarakat pelaku Desa Wisata, serta dapat menggambarkan /memetakan pemanfaatan ruang di Desa Lerep pada masa pandemi.Keywords: activity, space, tourism village, pandemic